Justice through apologies : Remorse, reform, and punishment - Smith, Nick (Cambridge University Press, 2014)
"Consider the case of William Beebe, who drugged and raped eighteen-year-old Liz Seccuro at a University of Virginia Phi Kappa Psi party in 1984. Seccuro awoke the next day wrapped in a bloody sheet on the couch of the deserted fraternity house. She confirmed Beebe's identity by the mail on his dresser. Still bloodied and bruised, Seccuro reported the attack. Campus authorities and Charlottesville police treated her claim dismissively and obstructed her access to a proper investigation. Beebe claimed she had consented. Feeling stonewalled and hoping to move forward with the rest of her education and life, Seccuro stopped pursuing legal recourse.Twenty-one years later, Seccuro pulled out of her driveway en route to a vacation with her spouse and young child"--